Effects of Face and Background Color on Facial Expression Perception - Minami, Tetsuto; Nakajima, Kae; Nakauchi, Shigeki (Frontiers in Psychology, 2018)
Detecting others’ emotional states from their faces is an essential component of successful social interaction. However, the ability to perceive emotional expressions is reported to be modulated by a number of factors. We have previously found that facial color modulates the judgment of facial expression, while another study has shown that background color plays a modulatory role. Therefore, in this study, we directly compared the effects of face and background color on facial expression judgment within a single experiment. Fear-to-anger morphed faces were presented in face and background color conditions. Our results showed that judgments of facial expressions was influenced by both face and background color. However, facial color effects were significantly greater than background color effects, although the color saturation of faces was lower compared to background colors. These results suggest that facial color is intimately related to the judgment of facial expression, over and above the influence of simple color.